The heritage turn in China : the reinvention, dissemination and consumption of heritage - Ludwig, Carol; Wang, Yi-Wen; Walton, Linda A. (Asian heritages (Amsterdam, Netherlands), 2020)
"This edited volume focuses on heritage discourse and practice in China today as it has evolved from the 'heritage turn' that can be dated to the 1990s. Using a variety of disciplinary approaches to regionally and topically diverse case studies, the contributors to this volume show how particular versions of the past are selected, (re)invented, disseminated and consumed for contemporary purposes. These studies explore how the Chinese state utilises heritage not only for tourism, entertainment, educational and commercial purposes, but also as part of broader political strategies on both the national and international stage. Together, they argue that the Chinese state employs modes of heritage governance to construct new modernities while strengthening collective national identity in support of both its political legitimacy and its claim to status as an international superpower. The authors also consider ways in which state management of heritage is contested by some stakeholders whose embrace of heritage has a different purpose and meaning."--